2020
DOI: 10.1177/1479973120912821
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise during acute exacerbations of chronic obstructive pulmonary disease: Australian physiotherapy practice

Abstract: Evidence supports an important role for pulmonary rehabilitation (PR) after acute exacerbations of chronic obstructive pulmonary disease (AECOPD); however, the role of physical exercise during hospitalisation is less clear. This study evaluated Australian physiotherapy practice and clinical perspectives regarding exercise and physical activity for patients with AECOPD. A national survey of 123 Australian public hospitals was conducted from 2016 to 2017 using a purpose-designed survey measuring self-reported ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Differences between populations and pathophysiology of acute exacerbations, however, render it difficult to determine whether such findings would translate to people with AECOPD. Further enquiry into this area of practice would be of benefit to clinicians and patients, particularly in light of a recent study [26] that showed Australian physiotherapists frequently prescribe physical activity for patients with AECOPD, often in conjunction with huffing and coughing. This survey also showed referrals to pulmonary rehabilitation after discharge were very high, in-keeping with Australian guidelines [27] recommending that patients participate in pulmonary rehabilitation within two weeks of hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between populations and pathophysiology of acute exacerbations, however, render it difficult to determine whether such findings would translate to people with AECOPD. Further enquiry into this area of practice would be of benefit to clinicians and patients, particularly in light of a recent study [26] that showed Australian physiotherapists frequently prescribe physical activity for patients with AECOPD, often in conjunction with huffing and coughing. This survey also showed referrals to pulmonary rehabilitation after discharge were very high, in-keeping with Australian guidelines [27] recommending that patients participate in pulmonary rehabilitation within two weeks of hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Many, but not all, of these papers pertain to patients with acute exacerbations of chronic obstructive pulmonary disease, perhaps reflective of the ongoing challenges that acute healthcare providers face to optimally manage this patient group. Read the whole collection and you will gain valuable insights spanning a diverse range of study designs, exploration of issues via quantitative and qualitative methodologies, focused reports of physiotherapeutic practices from different countries across the globe, 5,6 updates regarding instrument validation (De Morton Mobility Index) for use in the acute hospital environment, 7 evaluations of biomarker utility 8 and clinical stratification 9 during acute exacerbations of interstitial lung disease and exploration of issues affecting rates of pulmonary rehabilitation uptake in the period after acute respiratory exacerbations. 10,11 Suffice to say, whether you are a clinician, researcher, healthcare policy maker or an individual affected by chronic respiratory disease, we hope you will find something that will appeal to your interests within this special collection.…”
mentioning
confidence: 99%